Evaluating the Performance of Jordanian Islamic Banks Using SWOT - Badarin, Abdalla; Khreis, Najeeb (Jordan Journal of Islamic Studies, 2023)
The study aimed to evaluate the performance of Jordanian Islamic banks using SWOT analysis to identify strengths, weaknesses, opportunities, and threats. The sample included all Jordanian Islamic banks. The study adopted a descriptive and analytical approach, starting with an analysis of the internal and external banking environment, as well as the legislative environment. It also analyzed the intellectual and financial performance indicators. The study found several strengths, including uniqueness in its adherence to Islamic principles, high profitability and liquidity levels, and low risk levels. On the other hand, it identified weaknesses such as deviating from its foundational principles, limited investment diversification, weak external presence, and insufficient contribution to economic development. Furthermore, the study highlighted opportunities, such as the possibility of increasing profitability, enhancing investment diversification, exploiting national investment opportunities, and improving international presence. It also identified threats, such as limited investment opportunities, the need for developing Sharia-compliant banking products, and the importance of improving service quality. The study recommended that Islamic banks address weaknesses, enhance strengths, capitalize on available opportunities, and proactively address expected threats.